Institutional obstetric violence: a question about women’s rights (Research, Society and Development, 2021)
Objective: This integrative review aims to understand through the literature how the institutional process of obstetric violence in women was established, taking into account that this phenomenon is recognized through different types of aggression that can occur in the context of pregnancy, childbirth, puerperium, such as also in situations of abortion, post-abortion and reproductive cycle.  Methodology: This is an integrative literature review where articles were selected using the platforms of SciELO, PUBMED and MEDLINE and only articles published in Portuguese, English or Spanish and a primer, were chosen for the sample space of the research, which portrayed the theme related to the occurrence of obstetric violence and articles published and indexed in these databases in the last 21 years.  In this integrative review, we carried out activities to search for information, compile and register the selected articles.  Results and discussion: Obstetric violence is still a reality, occurring mainly with low-income and low-educated women, expressing itself through verbal abuse, unnecessary procedures, among other ways.  This is due to the lack of preparation of the health team, laws and women's lack of awareness.  Conclusion: Obstetric violence is characterized by inappropriate practices against women during pregnancy.  The psychological damage to this parturient is notorious.  To reduce this reality, bills that support women, their awareness during prenatal care, and a more humanized training of future health professionals are needed.